The Strength of the Medial Olivocochlear Reflex in Chinchillas Is Associated With Delayed Response Performance in a Visual Discrimination Task With Vocalizations as Distractors - Vicencio-Jimenez, Sergio; Bucci-Mansilla, Giuliana; Bowen, Macarena; Terreros, Gonzalo; Morales-Zepeda, David; Robles, Luis; Délano, Paul H. (Frontiers in Neuroscience, 2021)
The ability to perceive the world is not merely a passive process but depends on sensorimotor loops and interactions that guide and actively bias our sensory systems. Understanding which and how cognitive processes participate in this active sensing is still an open question. In this context, the auditory system presents itself as an attractive model for this purpose as it features an efferent control network that projects from the cortex to subcortical nuclei and even to the sensory epithelium itself. This efferent system can regulate the cochlear amplifier sensitivity through medial olivocochlear (MOC) neurons located in the brainstem. The ability to suppress irrelevant sounds during selective attention to visual stimuli is one of the functions that have been attributed to this system. MOC neurons are also directly activated by sounds through a brainstem reflex circuit, a response linked to the ability to suppress auditory stimuli during visual attention. Human studies have suggested that MOC neurons are also recruited by other cognitive functions, such as working memory and predictability. The aim of this research was to explore whether cognitive processes related to delayed responses in a visual discrimination task were associated with medial olivocochlear function. In this behavioral condition, chinchillas held their responses for more than 2.5 seconds after visual stimulus offset, with and without auditory distractors, and correlated the accuracy of these responses with the magnitude of the MOC reflex. We found that the animals’ performance decreased in presence of auditory distractors and that the results observed in MOC reflex could predict this performance. The individual MOC strength correlated with behavioral performance during delayed responses with auditory distractors, but not without them. These results in chinchillas, suggest that MOC neurons are also recruited by other cognitive functions, such as working memory.